Optimizing the Performance of Unit I-Dik III Tipikor Polres Kudus in Handling Corruption Crimes to Improve Corruption Case Resolution - Dirgantara, Fakhri Taruna (Advances in Police Science Research Journal, 2024)
The criminal act of corruption has become a factual threat that has a comprehensive impact on the life of the nation and state. Polri has a strategic role in enforcing the law on corruption. Polres kudus is a working unit of the Indonesian National Police which participates in enforcing the law on corruption through the role of the Unit Idik III Tipikor Polres Kudus. However, in practice there are problems related to the difficulty of achieving the target of settling corruption cases.This research will discuss the optimization of the performance of the Unit Idik III Tipikor Polres Kudus in handling corruption crimes in order to improve the settlement of corruption cases. This study uses a qualitative approach with a case study type of research. The focus of the research was on the performance and the implementation in handling of criminal acts of corruption at the Unit Idik III Tipikor Polres Kudus. Research on performance is carried out based on the perspective of the balanced scorecard.